Los mitos y su influencia en el cultivo de los productos Achuar con los estudiantes del 9no año de educación básica en el CECIB Mukuink año lectivo 2011-2012. - Pinchu Tsere, Pinchu Hernán (2012)
Currently learning and practice, the Achuar keep forgetting more and more, especially for the new generation. For connoisseurs-as in my community, I was interested to know and deepen the mythological beliefs of the Achuar crops in CECIB "Mukuink" Wichim Achuar community, so that young people know the beliefs and recovered what is ours. This does not mean that the subject of "Education mythology and its influence on the culture of the Achuar products with students ..." is completed or exhausted in a definitive way, but it requires some changes that will be taking over his application, as the coexistence and needs that may arise.